1992
DOI: 10.1111/j.1751-0813.1992.tb07490.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypotrichosis in Poll Dorset sheep

Abstract: PJ Mylrea References Dolling CHS and Brooker MG (1966)JHered 5787 Lofstedt J (1983) Vet CIin North Am ( h r g e Anim Pracf) 5: 427 Nel JA (1964) S Afr JAgric Sci 7 875 Popva-WassinaET (1931)5Hered22 91 Yager JA and Scott DW (1985) In Paihology of Domestic Animals, edited by Jubb KVF, Kennedy PC and Palmer N, 3rd edn, Academic Press, London, voll,p425

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The literature reports a few cases of congenital hypotrichosis in the ovine breeds Australian Polled Dorset [7,10], Karakul [11], and Valle del Belice [9]. So far no molecular study has been carried out in the ovine species.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports a few cases of congenital hypotrichosis in the ovine breeds Australian Polled Dorset [7,10], Karakul [11], and Valle del Belice [9]. So far no molecular study has been carried out in the ovine species.…”
Section: Introductionmentioning
confidence: 99%
“…These include hypotrichosis in the Arabian horse and its crosses, and mane and tail hair dystrophy in the Appaloosa (Fadok 1995b). Follicular dysplasias causing hypotrichosis and alopecia are reported in other species including the cow (Miller and Scott 1990;Mansell 1999), sheep (Mackie and McIntyre 1992) and dog (Miller 1990;Beco et al 1996). However, to date, no report on cases in the horse has been published, although anecdotal evidence exists for its occurrence (Scott 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other histologic examinations have demonstrated a decrease in follicle density, skin thickness, hair diameter, and size and number of sweat and sebaceous glands (Bracho et al, 1984;Hanna and Ogilvie, 1989). Becker et al (1963) reported that sweat glands were dilated and cystic while others observed normal sweat glands (Mackie and McIntyre, 1992). Other findings in sheep include an absence of fibers in follicles, keratotic follicles, hypertrophy and hyperplasia of sebaceous glands and epidermis, and epidermal hyperkeratosis (Mackie and McIntyre, 1992).…”
mentioning
confidence: 99%
“…Becker et al (1963) reported that sweat glands were dilated and cystic while others observed normal sweat glands (Mackie and McIntyre, 1992). Other findings in sheep include an absence of fibers in follicles, keratotic follicles, hypertrophy and hyperplasia of sebaceous glands and epidermis, and epidermal hyperkeratosis (Mackie and McIntyre, 1992).…”
mentioning
confidence: 99%